Role of Interleukin-6 in Lung Complications in Patients With COVID-19: Therapeutic Implications - Smetana, Karel; Brábek, Jan (In Vivo, 2020)
COVID-19 is viral respiratory infection with frequently fatal lung complications in the elderly or in people with serious comorbidities. Lung destruction appears to be associated with a cytokine storm related to an increased level of interleukin-6 (IL6). Therapeutic targeting of the interleukin-6 signaling pathway can attenuate such a cytokine storm and can be beneficial for patients with COVID-19 in danger of pulmonary failure. This article demonstrates the importance of IL6 in progression of disease and the possibility of inhibition of IL6 signaling in COVID-19 therapy.
Keywords: plíce; antivirové látky; signální transdukce; Receptors, Interleukin-6; virové receptory; syndrom uvolnění cytokinů; antiflogistika; klinické zkoušky jako téma; receptory interleukinu-6; Receptors, Virus; Cytokine Receptor gp130; monoklonální protilátky; Humans; lidé; Antibodies, Monoclonal; cytokinový receptor gp130; Lung; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Indoles; Coronavirus Infections; interleukin-6; pandemie; koronavirové infekce; Clinical Trials as Topic; virová pneumonie; Pandemics; Cytokine Release Syndrome; Interleukin-6; imunoterapie; Anti-Inflammatory Agents; Antiviral Agents; Pneumonia, Viral; Immunotherapy; Signal Transduction; indoly